Comparison the effects of arginine and sodium nitroprusside on the vase-life of Polianthes tuberosa L. cut flowers - Fatemeh Nasibi; Homayoun Farahmand; Hakimeh Oloumi; Leila Malekpourzadeh; Soudabeh Nourzad (Scientific Reports)
Abstract Tuberose (Polianthes tuberosa) is a fragrant bulbous ornamental plant valued for its aesthetic appeal but constrained by its short postharvest vase life. This study investigated the effects of arginine (Arg) and sodium nitroprusside (SNP), applied at concentrations of 1, 5, and 10 µM, on key postharvest traits of tuberose cut flowers. Using a completely randomized design with five replications under controlled conditions, we assessed flower opening, wilting, and abscission alongside antioxidant responses. The results revealed that both Arg and SNP markedly enhanced floret opening in the initial days, with 5 µM Arg and 10 µM SNP showing the strongest effects. These treatments also significantly suppressed flower abscission and wilting, maintaining floral quality throughout the experimental period. Enzymatic (CAT, GPX, APX) and non-enzymatic (PAL-mediated phenolic) antioxidant activity increased, while PPO activity decreased, reflecting reduced oxidative damage. Overall, Arg demonstrated comparable efficacy to SNP and may operate via non-nitric oxide mechanisms. Given its performance and eco-safety profile, especially at 5 µM, Arg presents a safe alternative to SNP avoiding the risk of cyanide release.